Directly observed treatment increases drug compliance in lymphatic filariasis mass drug administration - Rosanti, Tutik Ida; Mardihusodo, Sugeng Juwono; Artama, Wayan T. (Universa Medicina, 2016)
Backgroud. Mass drug administration (MDA) has been one of the strategies for lymphatic filariasis elimination. Since the start of implementation in 2011 in Pekalongan, no study on MDA acceptability has yet been done. The objectives of the study were to determine the microfilaria rate (mf rate) and the risk factors of drug compliance in the MDA program. MethodsA longitudinal study was conducted at Pabean region, Pekalongan City. There were 90 household heads as subjects, who were selected by proportional cluster random sampling. Microfilaria rate (mf rate) was determined by finger blood examination. Drug compliance was measured using questionnaires and observation sheets. Drug compliance observers, filariasis counseling participation, and presence of filariasis patients were factors influencing drug compliance. ResultsMf rate in 2015 was 1.35% and drug compliance rate was 86.80%. Reasons for failing to take drugs were fear of side effects (50%), refusals (25%), laziness (16.7%), and perceiving the drug to be useless (8.3%). The chi-square test shows a significant difference between the presence of drug compliance observer and compliance (p=0.006). Filariasis counseling participation and presence of filariasis patients did not show a significant difference with drug compliance (p= 0.986).ConclusionsFamilies as the source of observers was associated with increased filariasis drug compliance. It is therefore essential to address the issues linked to low compliance to make the program more efficient and achieve the goal of filariasis elimination.